COMPARISSON OF THE RESULTS OF PROCESSING OF CCD OBSERVATIONS OF SELECTED OPEN CLUSTERS - Protsyuk, Yu. I.; Kovalchuk, O. M.; Andruk, V. M. (Одеські астрономічні публікації, 2019)
Observations of open clusters at the Re- search Institute “Mykolaiv Astronomical Observatory” (RI MAO) were performed using the KT-50 telescope (D=500mm, F=3000mm) in 2011 – 2018. As the light re- ceiver, a CCD camera Apogee Alta U9000 (3K x 3K, FOV 42.6' x 42.6') in short drift scan mode was used. In short drift scan mode each observation consisted of several CCD frames with partial overlap in right ascension. All observa- tions were performed using R light filter. The exposure time was 20 seconds for all frames. All previous astromet- ric processing was carried out by the Astrometrica program and UCAC4 reference catalog. Using this data we received two catalogs of positions of 4.2 million stars (J2013.6) and 3.3 million starts (J2017.3) in the vicinity of open clusters with accuracy (0.03-0.07)". Unfortunately, current version of Astrometrica program have problem with data reduction with Gaia reference catalog in areas with big star density, like vicinity of open clusters near the plane of the Galaxy. At this article, we compared our old results with the new one for several open clusters which carried out with the author's set of programs with primary processing in the MIDAS environment. As reference stars the Tycho2, UCAC4 and Gaia DR2 catalogs were used. The reduction of 548 frames was performed using a polynomial of the third degree. The results obtained by author programs with reference catalogs UCAC4 and Gaia, showed good con- vergence. Several catalogs of positions of stars up to 17.5 m was obtained. The accuracy of the catalogs is σ RA =0.027" and σ Dec =0.033" for Gaia reference catalog and σ RA =0.032" and σ Dec =0.036" for UCAC4 reference catalog. At the same time, the accuracy of intraframe processing with the Gaia reference catalog turned out to be near 2 times better than the analogous one with the UCAC4 catalog. The compari- son showed the possibility of receiving more good results with Gaia reference catalog.